The Mediterranean Outflow Water: Transformations and Pathways into the Gulf of Cádiz - Gasser, Marc (Universidad Politécnica de Cataluña, 2018)
Memoria de tesis doctoral presentada por Marc Gasser i Rubinat para obtener el título de Doctor por la Universitat Politècnica de Catalunya (UPC), realizada bajo la dirección del Dr. Josep Lluís Pelegrí Llopart del Institut de Ciències del Mar (ICM-CSIC).-- 166 pages [EN] The Mediterranean Outflow Water (MOW) is a dense (¿>1028.5 kg/m3), saline (38.5 g/kg) ocean stream originated in the evaporative Mediterranean basin flowing westward past Espartel Sill as a fast (>1 m/s) and often unstable (as indicated by its gradient Richardson number) gravity current. During its descense into the Gulf of Cadiz, the MOW entrains the overlying North Atlantic Central Water (NACW), until the density difference between both water masses vanishes, and reaches its equilibrium depth. Inertia, Coriolis and frictional forces (both internal and with the bottom), as well as pressure gradients (associated with both seafloor slope and density gradients), play varying roles throughout the MOW’s trajectory. In particular, bathymetric steering due to contouritic, turbiditic and diapiric structures controls the early trajectory of the outflow. Using both historic and current hydrographic data, and a new high-resolution bathymetry of a critical region west of Espartel Sill, we examine the hydrographic characteristics of the MOW and the mechanisms that set its pathway. Our study is complemented with the proposal of simple models that help explain pbservations of vertical mixing in the Strait of Gibraltar and the behavior of the MOW as a gravity current within the Gulf of Cádiz, as well as with a new tool, based on water tributaries methods, that assesses the relative impact of both seafloor slope and Coriolis force in steering the outflow [CAT] La sortida d'aigua mediterrània (MOW) és un corrent oceànic dens (¿>1028.5 kg/m3) i salí (38.5 lg/m3) originat en la conca evaporativa de la Mar Mediterrània que flueix passant la baixa d'Espartel en forma d'un corrent de gravetat molt ràpid (>1 m/s) i sovint inestable (tal i com indica ...